Application of the Amtsilati Method in Reading the Yellow Book - Bachtiar Hariyadi (STAI Miftahul Ula Nganjuk, 2018)
Studying the yellow book cannot be separated from the world of pesantrenan because it becomes a mandatory book (Al-Pole Al-Mukarrarah) which is almost sacred since the fifth century, XIII H, XI and XIII M and to this day continues dynamically in boarding schools especially those in pondok Salaf boarding school. This research formulates to describe the application of the Amtsilati method. The approach used in this study is a qualitative descriptive approach with data sources obtained through interview and documentation observations. From the results of the study it can be concluded that the application of the Amtsilati method in the learning of Nahwu Shorof to accelerate the study of the yellow book is good enough to be seen from the way of its application. For this reason the application of the Amtsilati method for a quick way to learn the Yellow Book at Pondok Pesantren X by presenting a professional teacher from the Amsilati method as a teacher.